The Impact of Socialization Influences on Teaching Career Choices Through Self-Perception of Education Study Program Students in FEB UNESA - Pratiwi, Adelia; Pahlevi, Trieninda (Universitas Negeri Surabaya, 2025)
Phenomenon/Issue : Students in education programs at FEB UNESA face various factors influencing their decision to pursue teaching careers. Despite many external and internal influences, socialization and self-perception play key roles in shaping these choices. Purpose: To analyze the influence of socialization on teaching career choices through self-perception among students of the Education Study Program at FEB UNESA. Research Methods : Quantitative explanatory research using a survey of 172 students (cohort 2021). Data were analyzed with Structural Equation Modeling (SEM) using the GSCA approach. Results : Socialization significantly affects teaching career choices both directly and indirectly through self-perception. Socialization also significantly impacts self-perception, and self-perception significantly influences teaching career choices. The model shows a strong explanatory power (R² = 0.838 for career choice; R² = 0.819 for self-perception). Research Contributions : This study extends the Social Cognitive Career Theory (SCCT) by highlighting the role of socialization and self-perception in career decision-making. The findings provide theoretical and practical insights for educational institutions to support students’ motivation and readiness for teaching careers